Quantification of Multi-Organ 11β-Hydroxysteroid Dehydrogenase Type 1 Enzyme Levels in a Zucker Fatty Rat Model: A PET Imaging Study - Jason Bini PhD; Jordan Strober PhD; Michael Kapinos BS; Ming-Qiang Zheng PhD; Songye Li PhD; Jim Ropchan PhD; Nabeel Nabulsi PhD; Yiyun Huang PhD; Rachel J. Perry PhD; Daniel F. Vatner MD, PhD; Richard E. Carson PhD (Molecular Imaging)
Background In rodents, 11β-hydroxysteroid dehydrogenase 1 (11β-HSD1) catalyzes the conversion of inactive 11-dehydrocorticosterone to the active hormone corticosterone. Dysregulation of intracellular glucocorticoid action is implicated in metabolic diseases. Assessing 11β-HSD1 enzyme levels in vivo may be key to understanding obesity pathophysiology. Objective We used a Zucker Fatty (ZF) rat model and [ 18 F]AS2471907 PET imaging to determine appropriate kinetic modeling methods and assess changes in 11β-HSD1 levels due to obesity in the liver, white and brown adipose tissue (WAT/BAT), and brain. Material and Methods To validate [ 18 F]AS2471907 PET in preclinical models, time-activity curves (TACs) were generated and kinetic modeling was performed with image-derived input functions (IDIFs) extracted from multiple locations. Quantitative estimates of radioligand binding were compared with ex vivo 11β-HSD1 protein expression. Validated quantitative PET kinetic modeling methods were then used to assess differences in 11β-HSD1 between lean and obese ZF rats. Metabolic disease status was confirmed with stable isotopes tracer studies of glucose and fatty acid metabolism. Results Obesity is associated with decreased brain 11β-HSD1 levels, measured by [ 18 F]AS2471907 PET, which correlated with measures of glucose and fatty acid metabolism. Conclusion We demonstrate that [ 18 F]AS2471907 PET can provide useful quantification of 11β-HSD1 levels in a rodent model of obesity.